Analisis Kemampuan Literasi Matematis Ditinjau Dari Self-Esteem Pada Materi Aritmatika Sosial Kelas VII SMP Koperasi Pontianak - Meri Andani; Utin Desy Susiaty; Hartono Hartono (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The aim of this research is to determine mathematical literacy abilities in terms of Self-Esteem in Social Arithmetic material for class VII Pontianak Cooperative Middle School. The subjects of this research were 27 grade VII students at Pontianak Cooperative Middle School. Of the 27 students, they will be categorized based on each student's abilities. This research began by providing a self-esteem questionnaire, a test of mathematical literacy skills, and interviews to categorize students' ability levels. After that, proceed with analyzing and categorizing based on self-esteem and level of mathematical literacy ability to determine the research subjects who will be interviewed by selecting 9 subjects consisting of 3 students who have high self-esteem, 3 students who have medium self-esteem and 3 students who have low self-esteem. From the research results, it was concluded that students who have high self-esteem meet the indicators: Ability to read and understand mathematical information, such as tables, graphs and diagrams, ability to create and use mathematical algorithms to solve problems and obtain accurate results, ability to create and use models mathematics to solve real life problems and the ability to develop mathematical concepts that are important in everyday life such as proportion, percentage and ratio. Students who have moderate self-esteem meet the indicators: Ability to read and understand mathematical information, such as tables, graphs and diagrams, ability to create and use mathematical algorithms to solve problems and obtain accurate results, ability to create and use mathematical models to solve real life problems . Students who have low self-esteem meet the indicators of the ability to read and understand mathematical information, such as tables, graphs and diagrams.